The comparison of productivity before and after cocoa national movement program (gernas) implemented in Mamasa Regency West Sulawesi - Amran, Arman; Paulus, Paulus; Warsidah, Warsidah (Anjoro: International Journal of Agriculture and Business, 2021)
In early 1990, Indonesia entered as the third-largest exporter in the world after Ivory Coast and Ghana. The number of cocoa farmers is estimated to be 1.4 million households, generally on a small scale, with an area of about two hectares of cocoa. The very high increase in cocoa prices during the economic crisis in the late 1990s contributed significantly to the poverty alleviation of cocoa farming communities, especially those in rural areas. Almost 20 percent of the national cocoa production comes from West Sulawesi Province. The Cocoa National Movement Program (Gernas) in West Sulawesi is a locomotive for community-based development as a holistic, integrated program involving stakeholders to increase productivity and quality and encourage the growth of the cocoa trade and industry. The Central Government subsequently carried it out formed the National Movement for the Improvement of Cocoa Production and Quality. The research showed that there had been a significant increase in cocoa productivity in Mamasa Regency, West Sulawesi, between before the National Movement Program and after its implementation through rejuvenetion, rehabilitation, and intensification programs. Rehabilitation activities are higher than those of rejuvenation and intensification. Rejuvenation increased cocoa production from 342.68 kg.ha–1.year–1 in 2008 to 605.05 kg.ha–1.year–1. Rehabilitation increased cocoa productivity from 332.47 kg.ha–1.year–1 in 2008 to 720.98 kg.ha–1.year–1 and intensification increased cocoa productictivity from 328.27 kg.ha–1.year–1 in 2008 to 531.45 kg.ha–1.year–1 during the program implemented.